Ultrasonic coating of nanofibrous webs: a feasible approach to photocatalytic water filters - ŞİMŞEK, RAMAZAN; POLAT, YUSUF (SPRINGER, 2016)
In this study, we introduce ultrasound-assisted coating as a simple means of functionalizing nanofibrous membranes for photocatalytic (PC) water filtration. TiO2 nanoparticles, which have an anatase crystalline phase with superior PC activity, were directly synthesized over TPU nanofibers and the coated membranes were characterized using scanning electron microscopy (SEM) and X-ray diffractometry. The SEM images confirmed that the addition of polyethylene glycol reduced the nanoparticle dimensions and yielded greater distribution over the nanofibers. UV-Vis analysis demonstrated that Ag decoration over the coating enhanced the PC performance by up to 69.4% following 2-h UV illumination.
Keywords: Nanofibers; Ultrasonic; Coating; Photocatalytic; POLYETHYLENE-GLYCOL; METHYLENE-BLUE; TIO2; DEGRADATION; PHOTODEGRADATION; NANOPARTICLES; EVOLUTION; TITANIA; ANATASE